2015
DOI: 10.1109/map.2015.2453883
|View full text |Cite
|
Sign up to set email alerts
|

Beam-Scanning Reflectarray Antennas: A technical overview and state of the art

Abstract: A u g u s t 2 0 1 5 1045-9243/15©2015IEEE detailed overview of various design methodologies and enabling technologies for beam-scanning reflectarray antennas is presented in this article. Numerous advantages of reflectarrays over reflectors and phased arrays are delineated, and representative beam-scanning reflectarray antenna designs are reviewed. For limited field-of-view beam-scanning systems, utilizing the reflector nature of the reflectarray antenna and the feed-tuning technique can provide a simple solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(91 citation statements)
references
References 97 publications
0
91
0
Order By: Relevance
“…This results in the so-called reconfigurable reflectarray antennas, where one can exploit features such as beam steering. Recent reviews on tunable and beam-scanning reflectarray antennas can be found in [15,16].…”
Section: The Reflectarray Antennamentioning
confidence: 99%
“…This results in the so-called reconfigurable reflectarray antennas, where one can exploit features such as beam steering. Recent reviews on tunable and beam-scanning reflectarray antennas can be found in [15,16].…”
Section: The Reflectarray Antennamentioning
confidence: 99%
“…Fortunately, graphene can be introduced as the "switch" for terahertz-frequency devices because of its active complex conductivity. Some antennas take advantage of the graphene by making the frequency or the radiation pattern reconfigurable [17][18][19][20][21][22][23] such as the MIMO antennas, 17 leaky-wave antennas, 18,19 Yagi antennas, 20 microstrip quasi-Yagi antennas, 21 reflect-array antennas, 22 slot antennas, 23 and dipole antennas. 24,25 The antennas proposed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Reflectarray antennas have become a real alternative in transmission/reception systems whose requirements impose severe constraints in terms of radiation pattern, directivity or gain [3]. The underlying idea in reflectarrays is the substitution of the conventional conformed reflector: the reflective surface that transforms in a plane wave the wave coming from the feeder is replaced by a planar array of radiating elements with an adequate phase distribution at each array cell [3], [4]. The phase shifting strategy, which depends on the system topology and the final antenna specifications, is usually provided by either a reflective delay line circuit connected to each radiating cell or at the radiating element itself by varying the element size and shape [5].…”
Section: Introductionmentioning
confidence: 99%